Curriculum Development for Islamic Cultural History Subjects - Mokoagow, Friska; Yahiji, Kasim; Ondeng, Syarifuddin; Arif, Muh (Journal La Edusci, 2024)
This article examines three questions: How is the development of the SKI curriculum of KMA No. 183 Madrasah 2019, How is the Implementation of SKI subject curriculum development based on KMA No. 184 of 2019 in Madrasah and how are the results of the development and implementation of SKI subjects KMA No. 183 and 184 MTs Ma'Arif NU in 2019 in Toruakat. This research is a type of qualitative research that uses observation, observation, and documentation. Primary and secondary data are the data sources used in the research. Reduction, submission, and verification are the data collection methods used. The results show that real activities or other activities involved in the learning process, such as practical exercises, are a real form of how the curriculum can be applied. This is in line with the statement of the principal of MTs Ma'Arif NU Toruakat, which is located in the Bolaang Mongondow region, especially Dumoga or Toruakat. The purpose of the development and implementation of the 2019 PAI curriculum and KMA Arabic No. 183 is to gradually train students to understand the principles of Islam relating to aqidah morals, sharia, and the development of Islamic culture, so that students can fulfill their religious obligations properly whether to Allah SWT, humans, or the universe. The Madrasah Curriculum Implementation Guidelines, stipulated in KMA 184, were issued in 2019 with the aim of encouraging and establishing rules for innovation in the implementation of the madrasah curriculum and providing a legal umbrella to develop the uniqueness of madrasahs, strengthen character, fight educational corruption, and develop religious moderation in madrasahs.